Microwave-assisted, [Bmim]HSO4-catalyzed synthesis of tetrasubstituted imidazoles via four-component reaction - Duc, Dau Xuan; Lanh, Ho Thi (Vietnam Journal of Science and Technology, 2022)
Imidazole derivatives are one of the most important classes of nitrogen-containing five-membered heterocycles with a wide range of biological activities. Thus, the synthesis of these heterocycles has attracted intensive research interest. The classical Debus–Radziszewski reaction is one of the most facile and straightforward methods to synthesize 2,4,5-trisubstituted imidazoles and 1,2,4,5-tetrasubstituted imidazoles. Various catalysts have been developed for this synthesis to improve efficiency and reduce environmental pollution. Ionic liquids, green solvents for synthesis, have also been employed for this synthesis. Furthermore, the use of microwave irradiation, which can bring many advantages such as: high yield of products, simple work-up, improved selectivity, and clean reaction pathways, has also investigated for this method. Herein, we described the synthesis of tetrasubstituted imidazoles under microwave irradiation. The four-component reaction of benzil, aryl aldehyde, ammonium acetate, and primary amine was performed using ionic liquid [Bmim]HSO4 as the catalyst. Ten imidazole derivatives were furnished in high yield using an environmentally benign procedure. All of products were formed in a short time and simply purified by filtration and crystallization. Structures of all synthesized compounds were characterized by 1H and 13C NMR data analysis and by comparison with reported data. Interestingly, some synthesized compounds have been reported to possess antifungal activity on some fungi.